Sosialisasi Pemanfaatan Media Digital untuk Dokumentasi Budaya pada Sekolah Adat Sentani : Socialization of the Use of Digital Media for Cultural Documentation at the Sentani Traditional School - Sokoy, Fredrik; Poli, Agustina Ivonne; Idris, Usman (Assoeltan: Indonesian Journal of Community Research and Engagement, 2025)
he use of digital media for cultural documentation is an increasingly relevant strategy in the digital era, particularly in the context of indigenous communities with vulnerable oral and non-material cultural heritage. This community service activity aims to increase the capacity of the Sentani Traditional School community to document cultural heritage through digital media. Facing the challenges of low digital literacy and the risk of losing oral culture, this program was designed based on community participation and an anthropological approach. The service method consisted of outreach, technical training, and mentoring in the use of simple digital devices such as cameras and mobile phones to document local dances, music, and cultural narratives. The results of the activity demonstrated an increase in participants' understanding and skills in creating digital documentation based on local values. An internal cultural documentation team was also formed to support the program's sustainability. This initiative demonstrates that cultural preservation can be carried out adaptively through the synergy of technology, local wisdom, and cross-sector collaboration.